Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah (PAD) per Kabupaten di Provinsi Nusa Tenggara Barat Tahun 2014-2018 - Nuri Hikmahyanti; aris Soelistyo (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to analyze the factors that affect the Regional Original Income (PAD) per district in the province of West Nusa Tenggara. The variables used in this study are PAD, Total Population, GRDP, number of Industries, and Government Expenditures. The collection of data relating to the Total Population, GRDP, number of Industries, Government Expenditures, and Regional Original Income was obtained from BPS and DJPK in West Nusa Tenggara Province. The technique used in this study is panel data regression analysis using three methods, including the Common Effect Model, Fixed Effect Model, and Random Effect Model. The model chosen is the Common Effect Model. The results of this study indicate that the variables of Population, GRDP, number of Industries, and Government Expenditures have a significant effect on PAD.